Analisis Pengaruh Rasio Solvabilitas dan Rasio Likuiditas Terhadap Pertumbuhan Laba Pada Perusahaan Sub Sektor Perdagangan Besar yang Terdaftar di Bursa Efek Indonesia Periode 2014 – 2016 - Hestiani Pratiwi; Rodhiyah Rodhiyah (Universitas Diponegoro, 2018)
Profit growth of sub-sector trading corporates listed on IDX period 2014 - 2016 mostly been decreased but still, even are some experienced increased. The decline was due to people's purchasing power decreased. The purpose of this research is to identify the influence of solvency ratio (DAR and DER) and liquidity ratio (CR) to profit growth. Data used is a secondary data from financial reports and panels, using purposive sampling with corporate criteria that earn a profit in the period 2014 - 2016 amounted to 42 consisting of 14 corporates x 3 years. The method of analysis is linear regression and significance using SPSS version 19.0. Solvency ratio (DAR) has no effect on profit growth with significance (0,646> 0,05) and regression coefficient (0,280). Solvency ratio (DER) has no effect on profit growth with significance value (0,934> 0,05) and regression coefficient value (0,009). The ratio of liquidity (CR) has no effect on profit growth with significance (0,546> 0,05) and regression coefficient value (-0,010). It can be concluded that solvency and liquidity ratios together have no effect on profit growth with significance value (0,758> 0,05 and 0,395 <2,85). It is suggested that companies need to observe and manage sales and load leves to avoid the happening of consumptive action.